A 20-year global analysis of elite IRONMAN® performance - Mabliny Thuany; David Valero; Elias Villiger; Pedro Forte; Marilia Santos Andrade; Pantelis T. Nikolaidis; Ivan Cuk; Rodrigo Luiz Vancini; Katja Weiss; Thomas Rosemann; Sasa Duric; Beat Knechtle (Sport Sciences for Health, 2026)
Abstract Purpose To identify the best-performing nationalities and race locations for professional IRONMAN® triathletes, and to explore the best environmental conditions. Methods We collected and analyzed records from 6,848 professional finishers representing 37 countries participating in 54 IRONMAN ® race locations between 2002 and 2022. Information extracted includes athlete information (sex, country of origin, race location), performance (hh:mm:ss), and environmental conditions (i.e., water and air temperature). A non-linear machine learning predictive model was developed with race finish time as the predicted variable and sex, country of origin, event location, and the locations’ average air and water temperatures as predictors. Several model interpretability tools were used to assess the contribution of each predictor to the model’s predictions. All analyses, modeling, and visualizations were performed using Python. Results Among the top five, the fastest overall male race times were achieved by athletes from Ukraine (8.71±0.58 h), Portugal (8.79±0.41 h), Poland (8.94±0.68 h), Switzerland (8.98±0.48 h), and Estonia (9.00±0.67 h). The fastest overall female race times were recorded by athletes from Poland (9.37±0.35 h), Finland (9.53±0.64 h), Chile (9.70±0.33 h), Switzerland (9.71±0.55 h), and Denmark (9.78±0.59 h). The fastest overall race times were achieved at IRONMAN® Tallinn (9.01±0.67 h), and IRONMAN ® Switzerland Thun (9.02±0.38 h). The model identified sex as the most important predictor, followed by the athlete’s country of origin. For air temperature, the model predicted the best race times within a range of 19 to 27 °C. For water temperature, the model favored warmer temperatures for faster race time predictions. Conclusions The professional IRONMAN ® performance is influenced by a combination of geographical and environmental factors. European countries and race locations were consistently associated with superior performances, while favorable environmental conditions were characterized by relatively warm water temperatures and moderate air temperatures.